Modele wyboru dyskretnego z heteroskedastycznym składnikiem losowym przy ustalaniu akcji niezdominowanych przez rynek na GPW w Warszawie - Burzała, Milda Maria (Discrete choice models with heteroscedasticity of random terms in finding undominate stocks by market on GPW in Warsaw, 2006)
This paper studies the possibilities of the applications discrete choice models to find undominate stocks by the market. The return rate of these stocks is higher than the return rate of WIG index, but the risk is lower than the risk of WIG index. The most flexible model that can approximate any random terms is the mixed logit. One of specification uses a factor analytic structure. For that reason the author compares results of applications multinomial logit model and logit kernel model with factor analytic form. The analysis is based on the data from GPW in Warsaw between July 2001 and July 2005 and confirms better quality of the mixed logit model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 34-42